Medical insurance-related professionals’ identification of the benefits of the medical insurance system in Northeast China: a cross-sectional study - Zili Zhou; Huan Liu; Linghan Shan; Ye Li; Xin Zhang; Jiahui Wang; Zheng Kang; Mingli Jiao; Yanhua Hao; Yangguang Chen; Qunhong Wu (BMC Health Services Research)
Abstract Background The identification of the benefits of the medical insurance system (IBMIS) serves as an important indicator of the effectiveness of medical insurance policy implementation and provides valuable feedback during the ongoing reform phase of the medical insurance system (MIS). This research aims to analyze the IBMIS from the perspective of medical insurance-related professionals and to identify potential associate factors with IBMIS. Methods In 2021, we conducted a cross-sectional questionnaire survey (n = 1829) in Heilongjiang Province, located in Northeast China, to collect data. Interviewees were selected using a multi-stage stratified cluster random sampling method. A binary logistic regression model was employed to identify the factors influencing the IBMIS. Results Overall, 66% (1,207) of professionals associated with medical insurance exhibited a high IBMIS. The logistic regression model indicated that a high IBMIS was positively correlated with the following dimensions: policy capacity (OR = 1.562, 95% CI: 1.375–1.775), financial burden (OR = 1.512, 95% CI: 1.347–1.699), and convenience (OR = 1.300, 95% CI: 1.171–1.442). Four significant factors (P < 0.05) contributing to a high IBMIS include: “Relief of financial burden for people with serious diseases” (OR = 2.288, 95% CI: 1.740–3.007), “Medical insurance’s ability to address major problems that people expect” (OR = 1.565, 95% CI: 1.175–2.085), “Governance capacity of the medical insurance administrative agencies and management institutions” (OR = 1.472, 95% CI: 1.111–1.951), and “Effectiveness of governance for off-site medical reimbursement issues” (OR = 1.445, 95% CI: 1.036–2.014). Conclusion The policy capacity, financial burden, and convenience of the MIS have a positive impact on the IBMIS. Government departments can pay closer attention to these factors and formulate targeted intervention measures to improve the implementation effectiveness of medical insurance policies.